2019
DOI: 10.3389/fnint.2019.00035
|View full text |Cite
|
Sign up to set email alerts
|

Taste Responses in the Nucleus of the Solitary Tract of Awake Obese Rats Are Blunted Compared With Those in Lean Rats

Abstract: Taste perception changes with obesity but the underlying neural changes remain poorly understood. To address this issue, we recorded taste responses from single cells in the nucleus tractus solitarius (NTS, the first synapse in the central gustatory circuit) in awake, diet-induced obese [(DIO; ≥ 8 weeks on a high-energy diet (45%fat, 17% sugar; HED)], and lean rats. Rats were implanted with a bundle of microelectrodes in the NTS and allowed to recover. Water-deprived rats were allowed to freely lick various ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 63 publications
3
31
0
Order By: Relevance
“…More specifically, Thiebaud et al (2014) reported that hyperlipidemic diet in mice and associated obesity leads to a loss of olfactory sensory neurons and a decrease in olfactory function (Thiebaud et al, 2014). Moreover, it might be possible that the neural response to sensory input is blunted as it has been shown in taste processing (Weiss et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Thiebaud et al (2014) reported that hyperlipidemic diet in mice and associated obesity leads to a loss of olfactory sensory neurons and a decrease in olfactory function (Thiebaud et al, 2014). Moreover, it might be possible that the neural response to sensory input is blunted as it has been shown in taste processing (Weiss et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is emerging that the levels of salt, sugar, and fat in diets can alter taste sensation in humans (3)(4)(5), raising the question of whether these sensory changes may influence food intake, obesity, and metabolic disease (6,7). This idea is supported by a number of recent animal studies that found changes in taste, neural responses, and food preferences in rodents fed high-nutrient diets (8)(9)(10)(11)(12)(13). However, because of the complexity of the mammalian taste system and the lack of genetic tools, we know next to nothing about the molecular mechanisms through which diet composition affects taste sensation and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of diets high in sugar and fat decreases the perception of taste stimuli, influencing food preference and promoting food intake (Bartoshuk et al 2006;Sartor et al 2011;Kaufman et al 2018;Ahart et al 2019;May et al 2019;Weiss et al 2019) . Recent studies have examined the effects of these diets on the sensitivity of the peripheral taste system and the intensity of taste experience (Maliphol, Garth, and Medler 2013;Kaufman et al 2018;May et al 2019;Weiss et al 2019) , but how exactly taste deficits increase feeding behavior is not known.…”
Section: Introductionmentioning
confidence: 99%